1992
DOI: 10.1161/01.atv.12.12.1402
|View full text |Cite
|
Sign up to set email alerts
|

Aortic permeability to LDL as a predictor of aortic cholesterol accumulation in cholesterol-fed rabbits.

Abstract: The aim of this study was to investigate the possibility that the permeability characteristics of the arterial wall are related to the development of atherosclerosis. The in vivo regional variation of aortic permeability to iodinated human low density lipoprotein (LDL) in normal rabbits was compared with the regional variation in aortic cholesterol accumulation in cholesterol-fed rabbits. Aortas were divided into the aortic arch, thoracic aorta, and abdominal aorta, and each of these three parts was further su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
40
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 32 publications
(20 reference statements)
5
40
0
Order By: Relevance
“…This approach enabled us to precisely manipulate the compositions of the perfusate and superfusate solutions and carefully control arterial flow and hydrostatic pressure, hemodynamic parameters known to influence LDL flux into the artery wall. 7,8,37 The approach that we have taken enabled us to study the mechanisms of LDL flux into the artery wall and is a bridge between previous in vitro and cell culture experiments and experiments performed on whole-animal preparations. 5,18,38 The literature suggests that LDL is primarily modified in the arterial wall because of the large antioxidant capacity of the blood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach enabled us to precisely manipulate the compositions of the perfusate and superfusate solutions and carefully control arterial flow and hydrostatic pressure, hemodynamic parameters known to influence LDL flux into the artery wall. 7,8,37 The approach that we have taken enabled us to study the mechanisms of LDL flux into the artery wall and is a bridge between previous in vitro and cell culture experiments and experiments performed on whole-animal preparations. 5,18,38 The literature suggests that LDL is primarily modified in the arterial wall because of the large antioxidant capacity of the blood.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Sites of relative increase in LDL permeability have been identified in normal arteries 4 and can be induced by injury to the endothelium. [5][6][7][8][9] Alternatively, others have reported increased binding and decreased efflux of LDL from the vascular wall, even under conditions where LDL influx was not affected. 10,11 Therefore, LDL accumulation in the artery wall potentially occurs by several mechanisms, perhaps depending on the stage of atheroma formation.…”
mentioning
confidence: 99%
“…However, it is disturbing that an increased accumulation due to lipoprotein binding would lead to a flattening of the uptake-versus-time curve, which would give too low rather than too high an estimate of the fractional loss. One way to reconcile these observations is to introduce a "very fast equilibrating pool" or to adopt the concept of plasma contamination 23 ( Figure 5). This would lead to high uptake at early (3 hours) time points, thus restoring the shape of the curve, whereby the 2 types of errors might actually tend to cancel each other.…”
Section: Discussionmentioning
confidence: 99%
“…9 Still, arterial geometry and pressure are not sufficient to explain the localization of lesions, since major areas of high risk for atherosclerosis also occur away from the ostia and bifurcations 10 and some arteries subjected to normal arterial blood pressure are little affected by atherosclerosis. 3 -3 In fact, studies with experimental animals have demonstrated that low-density lipoprotein (LDL) metabolism, 11 endothelial permeability to LDL, 12 the glycoprotein coating of endothelial cells, 13 and the activity of acid cholesterol esterase 14 vary among vessels, and this variation could be related to differences in atherosclerosis susceptibility. A further aspect of arterial constitution that has been correlated with regional differences in the incidence of atherosclerosis is the degree of folding of the internal elastic membrane in humans, 15 which somehow reflects the amount of elastin in the vessel wall.…”
Section: ;1:115-124)mentioning
confidence: 99%